Odd-Electron Bonds - Clark, Timothy (ChemPhysChem, 2017)
The history and theory of one- and three-electron bonds are presented and discussed. It is shown that the dependence of the odd-electron bond energy on the difference in ionization potentials of the bonding partners must be corrected to include the ion-pairing energy for neutral odd-electron bonded complexes.
Keywords: abinitio calculations; bond theory; odd-electron bonds; radical reactions; reactive intermediates